THE IMPLEMENTATION OF THE STATE INDUSTRIAL POLICYON THE QUALITY OF PASSENGER ROLLING STOCK - Donchenko, A. V.; Fediushyn, Yu. M.; Loboiko, L. M. (Science and Transport Progress, 2005)
In article the concept of the state industrial politics on questions of quality is stated.